2022
DOI: 10.1038/s41538-022-00145-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with biogenic selenium nanoparticles alleviate oxidative stress-induced intestinal barrier dysfunction

Abstract: Selenium (Se) is an essential micronutrient that promotes body health. Endemic Se deficiency is a major nutritional challenge worldwide. The low toxicity, high bioavailability, and unique properties of biogenic Se nanoparticles (SeNPs) allow them to be used as a therapeutic drug and Se nutritional supplement. This study was conducted to investigate the regulatory effects of dietary SeNPs supplementation on the oxidative stress-induced intestinal barrier dysfunction and its association with mitochondrial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Likewise, selenium enhances mitochondrial respiration, increases mitochondrial content, and up-regulates mediators of mitochondrial biogenesis in placental cells and tissues [ 27 ]. Biogenic SeNPs can alleviate oxidative stress-induced mitochondrial dysfunction [ 54 ]. In this study, the autophagy of intestinal epithelial cells is significantly enhanced after oxidative stress and TM-induced ERS, as evidenced by the fact that the p-AMPK/AMPK, p-mTOR, LC3B-II/LC3B-I ratio, Beclin1, ULK1, PINK1, and Parkin are significantly increased, and that the expression of SQSTM1/p62 is decreased remarkably, accompanied by the occurrence of autophagosomes in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, selenium enhances mitochondrial respiration, increases mitochondrial content, and up-regulates mediators of mitochondrial biogenesis in placental cells and tissues [ 27 ]. Biogenic SeNPs can alleviate oxidative stress-induced mitochondrial dysfunction [ 54 ]. In this study, the autophagy of intestinal epithelial cells is significantly enhanced after oxidative stress and TM-induced ERS, as evidenced by the fact that the p-AMPK/AMPK, p-mTOR, LC3B-II/LC3B-I ratio, Beclin1, ULK1, PINK1, and Parkin are significantly increased, and that the expression of SQSTM1/p62 is decreased remarkably, accompanied by the occurrence of autophagosomes in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies showed that the increase in the abundance of these microorganisms is negatively correlated with the risk of disease induced by HFD ( 49 52 ). Interestingly, some studies showed that dietary selenium supplementation can improve their relative abundance ( 53 , 54 ). Therefore, the increase of PNS and selenium content jointly regulate the gut microbiota and reduce the negative effects of HFD.…”
Section: Discussionmentioning
confidence: 99%
“…or toluidine blue staining according to standard procedures. 31 Images of the slices were obtained using inverted microscope (Leica DMIL, Germany).…”
Section: Hande and Nissl Stainingmentioning
confidence: 99%
“…4 h prior to the end of the experiment, mice were given 400 mg/kg B.W. of FITC-dextran by gavage, 31 and the concentration of FITC-dextran in serum was measured with a Multi-Mode Microplate Reader (Bio-Rad, Hercules, USA).…”
Section: Intestinal Permeability Testmentioning
confidence: 99%
See 1 more Smart Citation